Difficulties faced by music students during the strine sectional rehearsals: A case study in UiTM / Nor Emalina Hamzah - Hamzah, Nor Emalina (2013)
This paper explored difficulties faced during string sectional rehearsal on 41 respondents who are string players that taking string sectional class in Faculty Music in UiTM. All the respondents described the situation and the difficulties faced during string sectional rehearsal. Result of the study revealed some students had a problem regarding attitude and commitment that can made rehearsals not effective.